Peningkatan Kemampuan Kognitif Dalam Mengurutkan Lambang Bilangan Melalui Media Kartu Angka - Akhmad Nayazik; Joko Suwignyo; Fara Meidika (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
Children’s characteristics can become absolute, and it can be understood in child’s development. Children’s characteristics is not formed by itself but needs to be directed and provided guidance in knowledge, so supports children's creativity. This research aims to improve the cognitive abilities of children for their ability of sorting numbers through playing card numbers in Group A TK Handayani VI Bantarbolang Village Wanarata Bantarbolang sub-district, Pemalang Regency. This is a classroom action research (CAR) with 2 cycles, each cycle consisting of stages of planning, implementation, observation, and reflection. The subjects of this study were 14 students of Group A. The data collection methods used were observation and documentation. The instrument was tested for its validity and reliability. The data analysis technique used was descriptive qualitative and quantitative descriptive. The result shows that the pre-action activities scored to 35%, and reached an increase in the first cycle to 50%, then reached to 80% in the second cycle. It can be concluded that the research hypothesis, which states the number symbol printed on the playing cards can improve the children’s cognitive ability, was accepted because it was evidence from the result that there was an increase to the higher score.